If the numerator of a fraction is increased by $2$ and the denominator by $1$, it becomes $\displaystyle \frac{5}{8}$ and if the numerator and the denominator of the same fraction are each increased by $1$, the fraction becomes equal to $\displaystyle \frac{1}{2}$. Find the fraction.

I tried, Let the numerator of the fraction be $x$, Let the denominator of the fraction be $y$ Therefore, Original fraction is $\displaystyle \frac{x}{y}$.

$$ \left\{ \begin{eqnarray*} \frac{x+2}{y+1}=\frac{5}{8} \\[2mm] \frac{x+1}{y+1}=\frac{1}{2} \\ \end{eqnarray*} \right. $$

What should I do now?

  • 1
    $\begingroup$ try to create the difference of the two equations (the first one minus the second one) $\endgroup$ – Thanos Darkadakis Jul 28 '14 at 13:00

That's a fine start. Now you've got two equations in two unknowns. $$\frac{x+2}{y+1} = \frac 58\tag{1}$$

$$\frac{x+1}{y+1} = \frac 12 \tag{2}$$

Now, we have to assume that $y+1 \neq 0$, given the information that's impossible, so we can take $(1)$ for example, and "cross multiply" to get: $$ 8(x+2) = 5(y+1) \iff \color{blue}{y + 1} = \frac{8(x+2)}{5}\tag{1}$$

From the second equation, we have

$$2(x+1) = \color{blue}{y+1}\tag{2}$$

That means $\color{blue}{y+1 = y+1}$, so that $$\frac {8(x+2)}5 = 2(x +1)\tag{3}$$

Now solve for $x$: $$\frac{8(x + 2)}5 = 2(x+1)\iff 5(x+1) = 4(x+2) \iff 5x+5 = 4x + 8 \iff x = 3$$ Then use $x=3$ to solve for $y$, using the fact that $y + 1 = 2(x + 1) \iff y = 2x + 1\implies y = 2(3) + 1 = 7$.

So the original fraction $$\frac xy = \frac 37$$

  • 3
    $\begingroup$ Also note that the second equation is in some sense "unnecessary" to solve the problem. 5-2 is 3, and 8-1 is 7, so 3/7 is easily found as the "most obvious" fraction that satisfies the first requirement. It also satisfies the second, so we're done without needing to use simultaneous equations. Of course, that isn't a general way to solve problems of this kind :-) $\endgroup$ – Steve Jessop Jul 28 '14 at 17:38
  • $\begingroup$ abhishekstudent - Is this clear now? $\endgroup$ – Namaste Jul 28 '14 at 19:03

We have the equations $$\frac{x+2}{y+1}=\frac{5}{8}, \ \frac{x+1}{y+1}=\frac{1}{2}=\frac{4}{8}$$ Hence $$x+1=4, \ y+1=8 \ \implies x=3, \ y=7$$ We are allowed to do so since $(x+2)-(x+1)=5-4$


$\dfrac{x+2}{y+1}=\dfrac{5}{8}$ and $\dfrac{x+1}{y+1}=\dfrac{1}{2}=\dfrac{4}{8}$

Dividing first equation by second equation you would get


This should be easy now..

  • $\begingroup$ How does the second row of your answer in any way follow from the first? $\endgroup$ – 5xum Jul 28 '14 at 12:32
  • $\begingroup$ @5xum : dividing first equation by second would give what i have concluded... $\endgroup$ – user87543 Jul 28 '14 at 12:34
  • 1
    $\begingroup$ Then say so in your answer, otherwise it is not really helping the OP. $\endgroup$ – 5xum Jul 28 '14 at 12:35
  • $\begingroup$ @5xum : please, that is not something that has to be mentioned... $\endgroup$ – user87543 Jul 28 '14 at 12:37
  • 1
    $\begingroup$ It does need to be mentioned to an OP that asks questions as basic as the one he asked. $\endgroup$ – 5xum Jul 28 '14 at 12:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.